Need to Study the Health Impact and Economics of Adult Vaccination with India in Focus - Dharamjeet S Faujdar; Sushil K Kaushik; Prafull Sharma; Arun K Yadav (Wolters Kluwer Medknow Publications, 2022)
Vaccination is undoubtedly the most effective and economical way of dealing with the diseases which can affect masses. Pediatric immunization against vaccine preventable disease (VPD) is being supported by most of the international health agencies, making them accessible and affordable to even the poorest of the countries. However, adult vaccination is needed to protect the most productive age group and improve the quality of life of the aging population and is left to those who can afford it. In most of the low- and middle-income countries including India, adult vaccination did not even find a mention in national vaccination policies. Although recommendation exists from various health associations in India for adult vaccination, they have not been given enough publicity as data on burden of VPDs and cost-effectiveness of these vaccines in adults are not available. Most of the general population and a substantial proportion of health care professionals in India lack awareness on the availability and need for these adult vaccinations. Now with improved childhood immunization and increased life expectancies, many diseases are showing epidemiological shift to the later part of life, thereby bringing the focus on adult immunization through the life course approach to reduce morbidity and mortality because of VPDs in adults and improve the quality of life of those left vulnerable because of aging or their existing medical condition.